Girls on the Fringe: The Writing Lives of Two Adolescent Girls. Issue 4 (3rd July 2016) - Pytash, Kristine E.
Abstract : Writing plays an important role in young adults' lives. It is tied to academic achievement and also provides young adults with a voice in social interactions, a way to express their feelings, and an opportunity to reflect on life events. This study explores the writing practices of 2 adolescent girls: Suzanne and Molly. On multiple occasions they had been suspended from school, attended an alternative school, and both had been incarcerated. Suzanne and Molly identified themselves as writers, as their personal writing served as a coping mechanism, a tool for communication, and a way to voice their lived experiences. Despite the power of writing in their lives, their in-school writing instruction was almost nonexistent.